Salience and taxation with imperfect competition - Kory Kroft; Jean-William P. Laliberté; René Leal Vizcaíno; Matthew J. Notowidigdo (Banco de México, 2022)
This paper studies commodity taxation in a model featuring heterogeneous consumers, imperfect competition, and tax salience. We derive new formulas for the incidence and marginal excess burden of commodity taxation highlighting interactions between tax salience and market structure. We estimate the necessary inputs to the formulas by using Nielsen Retail Scanner and Consumer Panel data covering grocery stores and households in the U.S. and detailed sales tax data. We estimate a large amount of pass-through of taxes onto consumer prices and find that households respond more to changes in prices than taxes. We also estimate significant heterogeneity in tax salience across households. We calibrate our new formulas using these results and conclude that essentially all of the incidence of sales taxes falls on consumers, and the marginal excess burden of taxation is larger than estimates based on standard formulas that ignore imperfect competition and tax salience.
Keywords: D12; D22; D43; D60; L13; H25; H71; 330; Sales taxes; Marginal Excess Burden; Incidence; Salience; Imperfect Competition